Estudio descriptivo del estado de salud bucal de poblaciones Mexicanas desfavorecidas en relación con su adherencia a la dieta mediterránea - Flores-Fraile, Javier (2024)
Background: Obesity in Mexico is an alarming problem that has been increasing in recent decades. Dietary factors make this pathology more common at younger ages and closely related to oral health. This study attempts to investigate the association between the oral health status of a Mexican population in the state of Yucatan and their dietary habits. Objective: This study explores the relationship between oral health-related quality of life and adherence to the Mediterranean diet in a disadvantaged population in the state of Yucatan, Mexico. Methods: The research was conducted in July 2023 in Merida, Yucatan (Mexico). The sample consisted of 109 individuals aged between 4 and 72 years old. Data analysis focused on factors such as body mass index (BMI), oral health-related quality of life, and adherence to the Mediterranean diet. Results: A notable presence of caries is observed in individuals with low adherence to the Mediterranean diet (Correlation coefficient 0.040, p=0.682). This underscores the potential interaction between oral health, obesity, and dietary habits. The mean Oral Health-Related Quality of Life (OHIP-14Sp) score was 13.19±13.57, median 8.00. Conclusions: This research adds to the increasing evidence that highlights the significance of a balanced diet in enhancing the oral quality of life for people. More research is necessary to explore preventive measures and treatment to raise awareness about oral health within the community.